Efficient Timing and Frequency Offset Estimation Scheme for OFDM Systems - 郭漪 葛建华 刘刚 张武军 (Transactions of Tianjin University, 2009)
A new training symbol weighted by pseudo-noise（PN） sequence is designed and an efficient timing and frequency offset estimation scheme for orthogonal frequency division multiplexing（OFDM） systems is proposed. The timing synchronization is accomplished by using the piecewise symmetric conjugate of the primitive training symbol and the good autocorrelation of PN weighted factor. The frequency synchronization is finished by utilizing the training symbol whose PN weighted factor is removed after the timing synchronization. Compared with conventional schemes, the proposed scheme can achieve a smaller mean square error and provide a wider frequency acquisition range.